A G‐type lectin receptor‐like kinase regulates the perception of oomycete apoplastic expansin‐like proteins. Issue 1 (21st January 2022) - Pi, Lei; Yin, Zhiyuan; Duan, Weiwei; Wang, Nan; Zhang, Yifan; Wang, Jinghao; Dou, Daolong
Abstract: Phytophthora capsici is one of the most harmful pathogens in agriculture, which threatens the safe production of multiple crops and causes serious economic losses worldwide. Here, we identified a P. capsici expansin‐like protein, PcEXLX1, by liquid chromatography‐tandem mass spectrometry from Nicotiana benthamiana apoplastic fluid infected with P. capsici . Clustered regularly interspaced short palindromic repeats/crispr associated protein 9 (CRISPR/Cas9)‐mediated PcEXLX1 knockout mutants exhibited significantly enhanced virulence, while the overexpression of PcEXLX1 impaired the virulence. Prokaryotically expressed PcEXLX1 activated multiple plant immune responses, which were BRI1‐associated kinase 1 (BAK1)‐ and suppressor of BIR1‐1 (SOBIR1)‐dependent. Furthermore, overexpression of PcEXLX1 homologs in N. benthamiana could also increase plant resistance to P. capsici . A G‐type lectin receptor‐like kinase from N. benthamiana, expansin‐regulating kinase 1 (ERK1), was shown to regulate the perception of PcEXLX1 and positively mediate the plant resistance to P. capsici . These results reveal that the expansin‐like protein, PcEXLX1, is a novel apoplastic effector with plant immunity‐inducing activity of oomycetes, perception of which is regulated by the receptor‐like kinase, ERK1. Abstract : Phytophthora capsici PcEXLX1, a novel apoplastic effector with plant immunity‐inducing activity, is an expansin‐like protein that is widely distributed and conserved in oomycetes. The Nicotiana benthamiana G‐type lectin receptor‐like kinase Expansin‐regulating kinase 1, Brassinosteroid‐associated kinase1 and Suppressor of bir1 1 regulate PcEXLX1 perception.